Rising prevalence and drug resistance of Corynebacterium striatum in lower respiratory tract infections - Li, Wei; Gao, Mingyue; Yu, Jinyan (Frontiers in Cellular and Infection Microbiology, 2025)
Corynebacterium striatum (C. striatum) is a Gram-positive bacterium commonly colonizing the skin and mucosa in healthy individuals and hospitalized patients. Traditionally regarded as a contaminant, C. striatum is now increasingly recognized as a potential cause of clinical infections, especially after the coronavirus disease pandemic. It has emerged as a pathogen implicated in severe infections, including pneumonia, bacteremia, meningitis, artificial joint infections, abdominal infections, and endocarditis. C. striatum has been reported in lower respiratory tract infections, mostly as a conditioned pathogen in immunocompromised individuals, particularly in those with chronic structural lung diseases, such as chronic obstructive pulmonary disease, leading to severe pneumonia or exacerbation of the existing disease and high mortality. Additionally, C striatum has been implicated in the community-acquired pneumonia among immunocompetent individuals and nosocomial lung infections, with evidence of person-to-person transmission through caregivers. C. striatum may exhibit multidrug resistance. Vancomycin, alone or in combination, is currently considered the most effective treatment for C. striatum. This review highlights the epidemiological characteristics, drug resistance mechanisms, diagnostics approaches, and treatment options for C. striatum lower respiratory tract infections to enhance clinician awareness and improve patient management strategies.